Coming Out of the Shadows? Housing Conditions of Irregular Migrant Workers in Spanish Agricultural Enclaves - López-Sala, Ana; Molinero-Gerbeau, Yoan (Calitatea Vieții, 2022)
The development of industrial agriculture in Spain has been accompanied, in recent decades, by an itinerant, recurrent and temporary mobility of immigrant workers between different productive enclaves. Although this group presents a wide internal diversity, an important segment of it is made up of workers in an irregular situation who participate in the seasonal circuit and who reside temporarily in some of these intensive production geographies. Their employment in conditions of informality makes them highly susceptible to extreme forms of labour exploitation, and to widespread difficulties in gaining access to a non-precarious legal status, which has turned their lives into an overlapping succession of chronic forms of social and labour exclusion. Additionally, the lack of political will, along with institutional and social racism has condemned many of these migrants to extreme forms of housing exclusion that has led them to reside in abandoned buildings, and spatially segregated informal settlements. In this article, we focus on this housing dimension, analysing the intersections between having an irregular status, performing agricultural work, and experiencing a subaltern spatial – residential situation. However, far from aiming to reproduce a passive vision of this issue, we analyse how migrants themselves have tried to respond to this situation. Recently, they have channelled a mobilization around the right to live in dignified conditions that has integrated demands for regularization, demands articulated around labour rights, and demands for the right to decent housing in the enclaves where they reside, thus contesting a deeply rooted policy of indifference that extends to the host societies.